Constant power load stabilization. (March 2018) - Mosskull, Henrik
Abstract: Stabilization of constant power loads (CPLs) fed through poorly damped input LC filters involves a trade-off between well damped filter quantities and small generated power modifications, where power modifications in general may be generated by internal CPL power control or by additional hardware. To simplify this trade-off, an explicit controller expression is presented, directly parameterized in terms of a damping factor. By also deriving damping factors corresponding to stabilization with minimal power modifications, tuning of stabilization becomes straight forward. Although applicable to most stabilization schemes, realization of the proposed stabilization is illustrated with an induction motor drive, using hardware-in-the-loop simulations. Highlights: Explicit handling of fundamental stabilization trade-offs. Control law with only three fixed design parameters. Control law valid at all operating points. Results applicable to a wide range of stabilization schemes.